Strategi Pengelola Informasi dan Dokumentasi Kepolisian Daerah Jawa Timur dalam Penanganan Gangguan Informasi pada Masyarakat - Priambodo, Agus Putra Sakti; Hendrawan, Muhammad Rosyihan; Suryadi, Suryadi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2020)
The aim of this research is to understand the role of Information and Documentation Officer at East Java Police Department in handling information disorder in the community. Furthermore, to understand the strategy of Information and Documentation Officer at East Java Police Department in preventing information disorder in the community, moreover the internal and external factors in handling information disorders. This research was located at Ahmad Yani 116 Street, Surabaya City. The type of the research is descriptive with qualitative approach. The data collection was done with interview, documentation, and observation methods. Subsequently, data analysis was done with interactive model (Miles, Huberman, and Saldana, 2014). Then, data validity test was completed using the triangulation method. Based on the research, it can be concluded that the strategy of Information and Documentation Officer at East Java Police Department in handling information disorder in the community is done by monitoring of cyberspace, engaging communities, evaluation, and take prevention by systematic and periodic outreach.